Herbal Medicines and Complementary Therapies: Their Role, Types and Applications - Sudiksha Sevani; Faiza Shaikh; Shraddha Bandagar; Dhanshree R. Karade; Raju Rathod (Emerging Trends in Personalized Medicines, 2025)
Medicinal plants are used in herbal medicine to treat and prevent illnesses. This includes the use of standardized and titrated botanical extracts in addition to common and traditional medicines from different cultures. The safety of a treatment may be suggested by its long history and deep cultural roots in traditional medical systems, but this does not always imply that it is effective. This is especially important in herbal medicine, since conventional treatments frequently use very low or ultra-low concentrations of active substances or are predicated on energy or magical concepts. In today’s globalized world, the relevance of evaluating the “transferability” of treatments across cultures is limited in clinical research. Instead, the focus should be on assessing efficacy and safety using the rigorous standards of mainstream clinical medicine. Another significant challenge in herbal treatments is the incomplete understanding of the precise composition of herbal extracts. To address this, modern biological technologies, such as pharmacogenomics, metabolomics, and microarray methodologies are essential for thoroughly evaluating the pharmacological properties and safety of herbal remedies. Given the widespread and increasing global use of plant-derived substances, it is unwise to rely solely on traditional practices or supposed millennia-old beliefs. Both explanatory and pragmatic studies play a crucial role in generating reliable data, benefiting both healthcare providers and patients. Traditional medicine encompasses the entirety of practices rooted in the theories, beliefs, and experiences of various cultures and historical periods. Often enigmatic or not easily explained, these practices are used to maintain health and support the prevention, diagnosis, management, and treatment of illnesses. In every country, traditional medicine is often influenced by magical or religious beliefs, as well as collective popular experience. The World Health Organization (WHO) is actively working to develop comprehensive guidelines for clinical research methodologies and the evaluation of the effectiveness of traditional medicine practices.
Keywords: Phytomedicine; Science based medicine; botanical medicine; herbal therapy; real world trials